Euphopias D–F from Euphorbia L.: quantum chemical calculation-based structure elucidation and their bioactivity of inhibiting NLRP3 inflammasome activation. Issue 12 (16th April 2021) - Shi, Qiang-Qiang; Zhang, Yu; Wang, Ting-Ting; Xiong, Feng; Zhang, Rui-Han; Li, Xiao-Li; Ji, Xu; Zhang, Xing-Jie; Wang, Wei-Guang; Xiao, Wei-Lie
Abstract : Euphopias D–F (1–3 ), three novel carbon skeleton diterpenoids with an inhibitory effect on NLRP3 inflammasome, were isolated and identified from the whole plants of Euphorbia helioscopia . Abstract : Euphopias D–F (1–3 ), three novel diterpenoids were isolated from Euphorbia helioscopia L. Comprehensive spectral analysis and a quantum chemical calculation strategy were employed to determine their structure. Compound 1 was defined by a unique caged tetracyclic[10.2.1.0 2, 10 .0 5, 9 ]pentadecane core skeleton, compound 2 was the first example of an 8, 9-norditerpenoid, possessing a tricyclic[8.3.0.0 2, 8 ]tridecane core skeleton, and compound 3 had a tricyclic[10.3.0.0 2, 8 ] pentadecane core skeleton. Biologically, compounds 1–3 exhibited a potential inhibitory effect on NLRP3 inflammasome. In particular, 1 could restrain the maturation of caspase-1 and regulate the secretion of cytokine interleukin-1β (IL-1β), thereby blocking GSDMD-mediated cell pyroptosis.